Er:YAG laser in hysterectomized women with stress urinary incontinence: a VELA retrospective cohort, non-inferiority study. (19th October 2020) - Erel, C. T.; Fistonić, I.; Gambacciani, M.; Oner, Y.; Fistonić, N.
Abstract: Objective: To test whether the erbium-doped yttrium aluminum garnet (Er:YAG) SMOOTH ® laser treatment efficacy on stress urinary incontinence (SUI) in hysterectomized patients is non-inferior to its efficacy in non-hysterectomized patients. Methods: In this real-world, retrospective cohort study performed in Turkey, Croatia and Italy, we enrolled a consecutive sample of 35 hysterectomized and 34 non-hysterectomized patients with SUI. We used the Er:YAG SMOOTH ® laser (Fotona, Slovenia) with a wave length of 2940 nm. The primary outcome was median reduction of SUI symptoms measured by the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short-Form (ICIQ-SF) with the non-inferiority margin defined as the minimum clinically important difference of ICIQ-SF (δ < 2.52 points). Results: In hysterectomized patients, the ICIQ-SF was reduced by 5 points (95% confidence interval 3–8; p < 0.001), a reduction of 45% (95% confidence interval 36–67%). After adjustment for baseline ICIQ-SF and five covariates, the reduction of symptoms in the hysterectomized group was not inferior to the reduction in the non-hysterectomized group. Conclusion: The Er:YAG SMOOTH ® laser treatment seems to improve the symptoms of SUI in hysterectomized women not clinically relevantly less than in non-hysterectomized women. It seems that the beneficial effect of Er:YAG SMOOTH ® laser treatment for SUI in hysterectomized women is time-limited.